2014
DOI: 10.1158/1535-7163.mct-13-0420
|View full text |Cite
|
Sign up to set email alerts
|

Novel Neutralizing Hedgehog Antibody MEDI-5304 Exhibits Antitumor Activity by Inhibiting Paracrine Hedgehog Signaling

Abstract: The hedgehog pathway has been implicated in the tumorigenesis, tumor progression, and metastasis of numerous human cancers. We generated the first fully human hedgehog antibody MEDI-5304 and characterized its antitumor activity and preclinical toxicology. MEDI-5304 bound sonic hedgehog (SHH) and Indian hedgehog (IHH) with low picomolar affinity and neutralized SHH and IHH activity in cellular mGLI1 reporter assays. The antibody inhibited transcription of hedgehog target genes and osteoblast differentiation of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Recently, a novel neutralising antibody acting on SHH and IHH with low picomolar affinity has been reported (Ref. 261 ). Moreover, two small molecules have been described; robotnikinin binds to and inhibits SHH protein (Ref.…”
Section: Inhibitors Of Hh-gli Signallingmentioning
confidence: 99%
“…Recently, a novel neutralising antibody acting on SHH and IHH with low picomolar affinity has been reported (Ref. 261 ). Moreover, two small molecules have been described; robotnikinin binds to and inhibits SHH protein (Ref.…”
Section: Inhibitors Of Hh-gli Signallingmentioning
confidence: 99%
“…Numerous studies reported the benefit of stromal modulation in enhancing chemo sensitivity in mouse models of PDA (19, 3841), however the use of Hh inhibitor in combination with chemotherapy agents in clinical trials with human subjects failed to show benefit (2023). The importance of Hh and c-Met pathways as potential PDA targets has been well documented (25, 4244).…”
Section: Discussionmentioning
confidence: 99%
“…Though, targeting both the HGF/c-Met and Hh pathways have shown promising results in pre-clinical studies, the benefits were not readily translated into to clinical trials with PDA patients (2023). Thus, we investigated the mechanisms of resistance to the single inhibitor of HGF/c-Met or Hh pathway and determined if targeting both the HGF/c-Met and Hh pathways simultaneously would overcome the resistance to single inhibitor treatment and lead to a more potent anti-tumor effect in combination with chemotherapy treatment.…”
Section: Introductionmentioning
confidence: 99%
“…In the report, two antibodies showed high affinity for SHh, 3H8 and 6D7 (MEDI-5304), with K d values of 36 pM and 5 pM, respectively; however, only MEDI-5304 had affinity for IHh with a K d of 34 pM, and neither had affinity for DHh [123]. Both antibodies were also shown to inhibit pathway signaling in Hh-dependent MEFs with IC 50 values of 3.4 and 5.3 nM respectively.…”
Section: Biologics As Hedgehog Pathway Inhibitorsmentioning
confidence: 99%
“…Both antibodies were also shown to inhibit pathway signaling in Hh-dependent MEFs with IC 50 values of 3.4 and 5.3 nM respectively. MEDI-5304 also decreased tumor volume in a compliant model of colorectal cancer, which mimics Hh-mediated paracrine cancer, in a dose-dependent manner with a modest overall growth reduction of 30–50% [123]. …”
Section: Biologics As Hedgehog Pathway Inhibitorsmentioning
confidence: 99%